Task Journal: An Alternative Medium in Teaching Reading Comprehension - Evi Agustina Sari; Yusri Yusri (ELTE Journal (English Languange Teaching and Education), 2013)
AbstractThis study was conducted to find whether or not there is a significant difference in reading comprehension achievement of students before and after being taught by using task journals. The writers used the weak experimental method with the one pre-test and post-test design. The sample for this study was the fourth semester students of English Department, State Polytechnic of Sriwijaya Palembang in theacademic year of 2012-2013. In collecting the data, the writers gave the students reading comprehension test.In this study the writers used matched t-test to analyze the data. In general the result of the study shows that teaching Reading subject using task journals is better and more appropriate for the students of English Department at the State polytechnics of Sriwijaya Palembang. It is found that there is a significant difference in reading ability of the students who were taught using task journals. It is seen from the comparison of the results of the pretest and the posttest. The observed t value which was taught using task journals was greater that the table t value at 0.05 level of significance. So the alternative hypothesis that there is a significant difference in students’ reading abilities which were taught using taskjournals was accepted.Keywords: Task journal, Reading Comprehension